Question

Asked Mar 14, 2019

57 views

Let h(x)=f(g(x)). If g(3)=−4, g′(3)=5, f(−4)=−6, and f′(−4)=4, find h′(3).

Do not include "h′(3)=" in your answer.

Step 1

We have to find derivative of h(x) at x=3 .

Information is given below:

Step 2

We will use chain rule to find derivative .

Rules is given below:

Step 3

With the help of chain rule we will find derivat...

Tagged in

Find answers to questions asked by student like you

Show more Q&A

Q: find the inverse of y from the function that is in the picture below

A: Giveninformation:The given function is

Q: Please help me on how to perform a test to determine if the equation converges.

A: The integral is given as

Q: How can I get the result? Which is the result?

A: The definite integral is given by,

Q: Find the values of the convergent series [from k=4 to infinity] E (2/3)3n-1 (-4/7)2n+3 *that E just ...

A: Given information:The given convergent series is

Q: Suppose that a particle has been shot into the air in such a way that the rate at which its height i...

A: v = 320 - 32tIf h represents the height of the particle at any time t, then:v = dh / dt = 320 - 2t

Q: At the indicated point for the function, find the following. You may use the numerical derivative fe...

A: Given information:The given function is

Q: y′=−2ex −9x2 +x+4 y(0)=6 Solve the initial value problem above. Do not include "y=" in your answer.

A: Solve the Initial Value Problem(IVP) for first degree differential equation is given.

Q: Determine the following indefinite integral. 324 dx, x> In 18 A dx 324- e2x Type an exact answer. Us...

A: The given integral is,

Q: Using disks or washers, find the volume of the solid obtained by rotating the region bounded by the ...

A: The given curve is y = x^2/3, x=1 and y=0.